2018
DOI: 10.1111/tbed.12862
|View full text |Cite
|
Sign up to set email alerts
|

A modified-live porcine reproductive and respiratory syndrome virus (PRRSV)-1 vaccine protects late-term pregnancy gilts against heterologous PRRSV-1 but not PRRSV-2 challenge

Abstract: The objective of this study was to determine the efficacy of a commercially available porcine reproductive and respiratory syndrome virus (PRRSV)-1 modified-live virus (MLV) vaccine against PRRSV-1 and PRRSV-2 challenge in late-term pregnancy gilts. Gilts were vaccinated with the PRRSV-1 MLV vaccine at 4 weeks prior to breeding and then challenged intranasally with PRRSV-1 or PRRSV-2 at 93 days of gestation. After PRRSV-1 challenge, vaccinated pregnant gilts had a significantly longer gestation period, signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…The protective role of NA is, however, limited in PRRSV vaccination [27]. Despite the low levels of NA elicited in response to PRRSV vaccination, vaccinated sows are still able to efficiently clear PRRSV viremia [94][95][96][97][98][99][100][101][102]. It is presumed that this was at least partially dependent on cell-mediated immunity, especially the host IFN-γ response, as IFN-γ is known to inhibit PRRSV replication [28,29].…”
Section: Criteria Of Vaccine Efficacy For Maternal Reproductive Failurementioning
confidence: 99%
“…The protective role of NA is, however, limited in PRRSV vaccination [27]. Despite the low levels of NA elicited in response to PRRSV vaccination, vaccinated sows are still able to efficiently clear PRRSV viremia [94][95][96][97][98][99][100][101][102]. It is presumed that this was at least partially dependent on cell-mediated immunity, especially the host IFN-γ response, as IFN-γ is known to inhibit PRRSV replication [28,29].…”
Section: Criteria Of Vaccine Efficacy For Maternal Reproductive Failurementioning
confidence: 99%
“…PRRSV-2 isolate, and cross-protection between PRRSV-1 and PRRSV-2 is considered insignificant, as demonstrated in different studies carried out in adult sows (38,39), boars (40,41), and piglets (42,43). This is probably due to the enormous genetic divergence between the two PRRSV species (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be mentioned that the characteristics of the PRRSV isolates used for the secondary exposure in some of those groups might have also contributed to the outcome of infection. Thus, the pigs of group A.2 were exposed to a PRRSV-2 isolate, and cross-protection between PRRSV-1 and PRRSV-2 is considered insignificant, as demonstrated in different studies carried out in adult sows ( 38 , 39 ), boars ( 40 , 41 ), and piglets ( 42 , 43 ). This is probably due to the enormous genetic divergence between the two PRRSV species ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the individual level, the efficacy of PRRS MLV is generally described as protective against both reproductive failure and respiratory disorders, providing multiple benefits including but not limited to the reduction of clinical signs, lessened macroscopic and microscopic lung lesion and viremia, shortened viral shedding period and reduced secondary bacterial infection [30,[92][93][94]. Reports in a gilts vaccination and late pregnant term challenge study have shown that MLV vaccination can improve the reproductive performance in sows and piglet health and overall viability, compared with unvaccinated sows [95][96][97].…”
Section: Homologous Protectionmentioning
confidence: 99%